Modelling impacts of drivers on biodiversity and ecosystems - Brotons, Lluís; Christensen, Villy; Ravindranath, N. H.; Cao, Mingchang; Chun, Jung Hwa.; Maury, Olivier; Peri, Pablo Luis; Proença, Vânia; Salihoglu, Baris (Intergovernmental Science-Policy Platform for Biodiversity and Ecosystem Services (IPBES), 2021)
Purpose of this chapter: Explores key issues in modelling impacts of changes in direct drivers on biodiversity and ecosystems; and critically reviews major types of models for generating outputs that are either directly relevant to assessment and decision-support activities, or are required as inputs to subsequent modelling of nature’s benefits to people. Key findings: 1-Models of biodiversity and ecosystem function are critical to our capability to predict and understand responses to environmental change; 2- There is a need to match biodiversity and ecosystem function model development to stakeholder and policy needs; 3- Biodiversity and ecosystem modelling depends heavily on our understanding of ecosystem structure, function and process and on their adequate representation in models; 4- Uncertainty in ecosystem dynamics is inherent in ecosystem modelling.